Antimicrobial resistance and bovine respiratory disease; a pharmacokinetic/pharmacodynamic approach to macrolide resistance - DeDonder, Keith David (Kansas State University, 2016)
Bovine respiratory disease (BRD) remains a major disease in beef production systems. The administration of antimicrobials for both the control and treatment of acute BRD is common. According to most published accounts, antimicrobial resistance among BRD pathogens is increasing; therefore, judicious antimicrobial usage is vital for continued efficacy. The introduction of a novel antimicrobial class has not occurred for well over a decade, therefore it is paramount to maximize efficacy of the antimicrobials currently available. The challenge is targeting the perfect scenario: maximizing clinical efficacy while minimizing antimicrobial resistance. The host-pathogen-drug interaction is very complex and despite current sophisticated technology, this interaction is still not well understood for many infectious diseases. This dissertation work sought to investigate the effects of the administration of a macrolide for both control and treatment of acute BRD on the prevalence of resistance among isolated Mannheimia haemolytica, Pasteurella multocida, and Histophilus somni. Whole genome sequencing of M. haemolytica was utilized to investigate the presence/absence of macrolide resistance genes and their relationship to the observed minimum inhibitory concentration. Cattle were sampled (plasma and pulmonary epithelial lining fluid) after administration of gamithromycin for drug concentration analysis. A non-linear mixed effects approach was used to fit a compartmental model to the resulting sparse pharmacokinetic data so that a complete time concentration curve could be simulated. From these curves, the CMAX and AUC were measured and used to calculate standard PKPD indices using the MIC values of the isolated bacteria. Clear associations between the use of gamithromycin for control and treatment of BRD and a statistically significantly increased likelihood of macrolide resistance were not found, possibly due to sample size limitations. The calculation of pharmacokinetic-pharmacodynamic indices found that a longer drug exposure was more closely associated with a successful treatment outcome, but there was not a statistically significant correlation. However, there were few clinical failures in this study giving further credence to the complexity of the in vivo system. There are many factors beyond pharmacokinetics/pharmacodynamics and MICs that contribute to the success of a treatment regimen for cattle suffering from BRD.
Keywords: bovine respiratory disease; antimicrobial resistance; gamithromycin; pharmacokinetic; pharmacodynamic; minimum inhibitory concentration; Veterinary Medicine (0778)